Light-driven core-shell fiber actuator based on carbon nanotubes/liquid crystal elastomer for artificial muscle and phototropic locomotion. (February 2022) - Yu, Yue; Li, Lele; Liu, Enping; Han, Xue; Wang, Juanjuan; Xie, Yu-Xin; Lu, Conghua
Abstract: Soft actuators controlled by untethered methods have aroused growing attention on account of their flexibility and controllability. Soft actuators shaped in a one-dimensional structure are highly desired in diverse practical applications. In this paper, we fabricate a new core-shell CNTs@LCE fiber soft actuator made of a liquid crystal elastomer (LCE) fiber coating with carbon nanotubes (CNTs) shell. Thanks to the outstanding photothermal conversion capacity of CNTs and remarkable thermal-contraction characteristic of LCE, the obtained core-shell CNTs@LCE fiber actuator can be controlled by near-infrared light with excellent phototropic bending to arbitrary directions, lifting loads more than 4600 times of its own weight and acting as artificial muscle to control the feature of biomimetic elbow and gripper with loads. More intriguingly, the core-shell CNTs@LCE fiber can fulfill unprecedented photo-driven phototropic locomotion including tracking the moving light source, climbing a slanted surface, and optically steering as well. The involved unique photo-driven phototropic movement mechanism has been revealed experimentally and theoretically, which is highly expected to guide the fabrication of other soft smart fiber actuators for advanced applications. Graphical abstract: Image 1 Highlights: New robust core-shell fiber soft actuators with excellent photo-powered actuation behaviors. Photo-fueled high-strength artificial muscle. Unprecedented photo-driven phototropic locomotion of 1D-shaped soft actuators with high controllability and adaptability.